Manajemen Keuangan Dalam Meningkatkan Ekonomi Ummat Masjid Di Lombok Timur - Masruron, Muhammad (Jurnal AlifLam Journal of Islamic Studies and Humanities, 2021)
Lombok is known as the island of a thousand mosques, although its geographical location is small, Lombok has its own specialties, its people always like to compete for charity through the construction of mosques. However, the mosque should be improved by prospering the mosque, some mosques are still not managed professionally so that the attention of the mosque is more organized. the principles of idaroh in the management of mosques start from (planning, organizing, implementing and controlling). On the one hand, the takmir of the mosque must pay attention to how to build understanding and awareness of giving, not burdening and not being burdened, paying attention to local wisdom, opening up space for creativity and participation, distribution of tasks and authority, encouraging, maintaining the feelings of the congregation, and transparency of mosque finances if this is done well. and true then the prosperity of the mosque can be realized. The economic empowerment of the people, is the main priority of the mosque management to pay attention to the congregation so that they are free from the snares of poverty and destitution, as explained in the Qur'an.